The Effect of Blast Furnace Slag/Fly Ash Ratio on Setting, Strength, and Shrinkage of Alkali-Activated Pastes and Concretes - Humad, Abeer M.; Kothari, Ankit; Provis, John L.; Cwirzen, Andrzej (Frontiers in Materials, 2019)
The aim of this study was to determine the effects of partial fly ash substitution in to a series of alkali-activated concrete based on a high-MgO blast furnace slag BFS. Mixes were activated with various amounts of sodium silicate at alkali modulus (mass ratio SiO2/Na2O) values of 1.0, 0.5 and 0.25. The results showed that, an increase in the fly ash content extended the initial setting time but had very little effect on the final setting time, although the early age compressive strength was decreased. The fly ash addition had no effect on the drying shrinkage but lowered the autogenous shrinkage. The mixes activated with sodium silicate at a lower alkali modulus showed a significantly higher autogenous shrinkage but lower drying shrinkage values. Severe micro cracking of the binder matrix was observed only for mixes without fly ash, activated with sodium silicate solution at higher alkali modulus. Decreasing the alkali modulus resulted in a higher autogenous shrinkage, less micro cracking and a more homogenous structure due to more extensive formation of sodium-aluminate-silicate-hydrate gel (N-A-S-H), promoted by the addition, and more extensive reaction of the fly ash.